HUBUNGAN TINGKAT STRES DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI PUSKESMAS RAWAT INAP CEMPAKA - Rina Lidia; Musafaah Musafaah; Ifa Hafifah (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2018)
Background:Elderly changes in the body system that causes an increase in blood pressure (hypertension) is affected by stress levels one of them. Objectives: Determine relationship between stress level and hypertension among elderly in Puskesmas Rawat Inap Cempaka. Method: Research was conducted on 7-13 February 2018 with cross sectional design with total sample was 54 elderly were taken using Purposive Sampling technique. The instrument used is Perceived Stress Scale Questionnaire (PSS) -10 to assess stress level and tensimeter to assess the pressure high blood pressure (hypertension). Results: Based on Chi-square test results, there is no relationship of stress level with the incidence of hypertension in elderly at Puskesmas Rawat Inap Cempaka. The value of p-value (p = 0.071). Discussion: There are several factors that affect hypertension, so the stress level factor can not be the single factor causing the occurrence of hypertension.